Optimization of endocrine pancreas fluorescence analysis using machine methods - Ivanenko, T. V.; Abramov, A. V.; Іваненко, Тарас Васильович; Абрамов, Андрій Володимирович (Запорізький державний медичний університет, 2022)
The study aims to establish the appropriate parameters of UV excitation intensity and permanent excitation time on the pancreatic islets photobleaching, the ratio of the intensity of the useful signal in the region of interest to the intensity of nonspecific background fluorescence. Materials and methods. The pancreas of three adult Wistar rats was fixed in Bouin solution (20 hours) and poured into paraplast after standard histological processing. The study was carried out on paraffin sections of the pancreas. The islets’ insulin and glucagon were determined by immunofluorescence method using monoclonal antibodies (Santa Cruz Biotechnology). The immunofluorescence reaction was studied using an AxioImager-M2 fluorescent microscope. AxioVision digital image analysis system was used for fluorescence imaging, and ImageJ 64-bit image analysis system was used for image quantification. 30 pancreatic islets with an area from 3000 μm2 to 5000 μm2 (8–13 % of the frame area) were analyzed. Results. Measurements carried out at constant values of hormone concentration in endocrinocytes showed a different estimate of the average fluorescence intensity for insulin and glucagon, which depended on the intensity of UV radiation. As the intensity of UV radiation increased, the average fluorescence intensity in the region of interest for insulin and glucagon increased, but when the camera exposure was corrected, it became almost the same. Regardless of this, the intensity of nonspecific background fluorescence increased monotonically. The use of the ratio of the logarithms of the background fluorescence of the drug and the fluorescence of endocrinocytes in the calculations gives a stable estimate of the relative concentration of hormones, which does not depend on the intensity of the selected UV radiation regime, as well as on the duration of UV irradiation of the drug. This makes it possible to neutralize the effect of photodynamic discoloration of the preparation caused by continuous irradiation. Methods for machine selection of the region of interest by various algorithms of the ImageJ program lead to different estimates of its area, integral, and average fluorescence values. At the same time, the result closest to the “ideal” interactive method of highlighting the area of interest for insulin and glucagon was shown by Otsu’s algorithm. Conclusions. In immunofluorescent examination of the pancreas, a moderate UV radiation mode should be selected, exposure correction of the CCD camera before taking each frame, and the total time for examining the visual field of the sample should be limited to 1–2 minutes. To highlight the area of interest for insulin and glucagon in automatic analysis, it is recommended to use the Otsu algorithm. To obtain a quantitative estimate of the average fluorescence intensity in the region of interest, it is recommended to use the ratio of the logarithms of the background fluorescence of the drug and endocrinocytes in the calculations. Мета роботи – встановити оптимальні параметри інтенсивності, тривалості безперервного УФ-випромінювання на фотодинамічне знебарвлення досліджуваних тканин підшлункової залози, а також на співвідношення інтенсивності корисного сигналу в зоні дослідження флуоресценції та інтенсивності неспецифічної флуоресценції фону. Матеріали та методи. Підшлункову залозу трьох дорослих щурів лінії Wistar фіксували в розчині Буена (20 годин) і заливали в парапласт після стандартної гістологічної обробки. Дослідження здійснили на парафінових зрізах підшлункової залози, в яких імунофлуоресцентним методом визначали інсулін і глюкагон у панкреатичних острівцях за допомогою антитіл виробництва Santa Cruz Biotechnology. Реакцію імунофлуоресценції вивчали на мікроскопі AxioImager-M2. Для зйомки флуоресценції використали систему аналізу цифрових зображень AxioVision, а для кількісного аналізу зображення – систему аналізу зображень ImageJ. Проаналізували 30 панкреатичних острівців площею 3000–5000 мкм2 (8–13 % площі кадра). Результати. Вимірювання, здійснені при постійних величинах концентрації гормонів в ендокриноцитах, показали різну оцінку середньої інтенсивності флуоресценції для інсуліну та глюкагону, що залежала від інтенсивності УФ радіації. З посиленням дії УФ радіації середня інтенсивність флуоресценції для інсуліну та глюкагону збільшувалась, але внаслідок корекції експозиції камери ставала майже однаковою. Незалежно від цього інтенсивність неспецифічної флуоресценції фону монотонно зростала. Використання в розрахунках відношення логарифмів флуоресценції фону препарату та флуоресценції ендокриноцитів дає стійку оцінку відносної концентрації гормонів, що не залежить від інтенсивності обраного режиму УФ радіації, а також від тривалості УФ опромінення препарату. Це дає змогу нівелювати ефект фотодинамічного знебарвлення препарату, спричиненого безперервним УФ опроміненням. Методи машинного виділення ділянки інтересу різними алгоритмами програми ImageJ дають різну оцінку її площі, інтегральної та середньої величини флуоресценції. Результат, наближений до «ідеального» інтерактивного способу виділення ділянки інтересу для інсуліну та глюкагону, показав метод сегментації Оцу. Висновки. Під час імунофлуоресцентного дослідження підшлункової залози слід обирати помірний режим УФ радіації, корегувати експозицію CCD камери перед кожним кадром, а загальний час дослідження поля зору зразка обмежити 1–2 хвилинами. Для виділення ділянки дослідження інсуліну та глюкагону під час автоматичного аналізу рекомендовано застосовувати алгоритм Оцу. Для отримання кількісної оцінки середньої інтенсивності флуоресценції у сфері дослідження рекомендоване використання в розрахунках відношення логарифмів флуоресценції фону препарату та ендокриноцитів.
Оптимізація флуоресцентного дослідження ендокринної частини підшлункової залози з використанням методів машинного аналізу
Ivanenko T. V. - ORCID ID: 0000-0001-6617-5178; Abramov A. V. - ORCID ID: 0000-0001-8520-2258.
Keywords: fluorescence microscopy; digital image analysis system; pancreas; флуоресцентна мікроскопія; система цифрового аналізу зображень; підшлункова залоза